25.1k views
3 votes
could someone help me out with 14? i tried it and I get that it uses chain rule and second derivative but I’m so lost please help

could someone help me out with 14? i tried it and I get that it uses chain rule and-example-1

1 Answer

6 votes

Answer:

d

Explanation:


(d)/(dt) (sinpt) = pcospt


(d)/(dt)(cospt) = - psinpt

Then

y = mcospt - nsinpt


(dy)/(dt) = - mpsinpt - npcospt


(d^2y)/(dt^2) = - mp²cospt + np²sinpt ← factor out - p² from each term

= - p²(mcospt - nsinpt) ← this is y

= - p²y

User Oleh Herych
by
6.1k points